Spirituality, Spontaneity, and Moral Charisma in Korean Confucianism - Ro, Young-chan (Journal of Korean religions, 2018)
The discussion on whether Confucianism is a religion may be an intriguing and important intellectual and academic issue. However, before we may engage in the whole spectrum of Confucian religiosity, including the ritual dimension of Confucianism, it would be fruitful to engage in the exploration of the ''spiritual'' aspect of Confucianism. The term ''spirituality'' is also so broad, ambiguous, and complex that we may not be able to define it in a simple and specific language. Furthermore, the way we understand ''spirituality'' may differ depending on the cultural context and religious traditions. In this article, I try to explore and appreciate the Confucian character of ''spirituality'' to understand the uniqueness of the Confucian and Neo-Confucian tradition, especially the Korean Neo-Confucian tradition represented by Yi Yulgok. My discussion of the Confucian form of spirituality includes: 1. the concepts of ''sacred'' and ''secular,'' arguing that Confucianism can best be represented by expressing ''sacred'' in ''secularity.'' 2. The arguement that Confucian ''spirituality'' is deeply embedded in the moral practice and intellectual investigation involved in the process of ''self-cultivation'' to realize the Confucian ideal of the ''superior man or person'' with spontaneity of moral charisma. 3. The notion that Confucian spirituality is found in the experience of the unity and continuity of the human to the cosmos and nature, representing the ''anthropo-cosmic'' or ''cosmo-anthropic'' idea of being human.